2020
DOI: 10.3389/fgene.2019.01377
|View full text |Cite|
|
Sign up to set email alerts
|

Data Mining and Expression Analysis of Differential lncRNA ADAMTS9-AS1 in Prostate Cancer

Abstract: Long noncoding RNAs (lncRNAs) play important roles in the regulation of gene expression by acting as competing endogenous RNAs (ceRNAs). However, the roles of lncRNAassociated ceRNAs in oncogenesis are not fully understood. The present study aims to determine whether a ceRNA network can serve as a prognostic marker in human prostate cancer (PCa). In order to identify a ceRNA network and the key lncRNAs in PCa, we constructed a differentially expressed lncRNAs (DELs)-differentially expressed miRNAs (DEMis)-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
3
31
1
Order By: Relevance
“…5 Bioinformatic analyses methods showed that ADAMTS9-AS1 may serve as crucial regulators for cancer progression, although its biological roles have rarely been investigated. [9][10][11] In the present study, ADAMTS9-AS1 demonstrated decreased expression in PCa and it was significantly correlated with a worse overall survival of PCa patients. With the knowledge that ADAMTS9-AS1 is expressed at low level in PCa, we then performed functional experiments to explore the roles of ADAMTS9-AS1.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…5 Bioinformatic analyses methods showed that ADAMTS9-AS1 may serve as crucial regulators for cancer progression, although its biological roles have rarely been investigated. [9][10][11] In the present study, ADAMTS9-AS1 demonstrated decreased expression in PCa and it was significantly correlated with a worse overall survival of PCa patients. With the knowledge that ADAMTS9-AS1 is expressed at low level in PCa, we then performed functional experiments to explore the roles of ADAMTS9-AS1.…”
Section: Discussionsupporting
confidence: 52%
“…Xing et al 10 also found that ADAMTS9-AS1 along with another 13 lncRNAs could predict the overall survival of colon adenocarcinoma patients. Wan et al 11 reported that ADAMTS9-AS1 could affect PCa cell behavior by regulating the microRNA-96 and PRDM16 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Different genetic conditions such as the different gene expressions (DGEs) can lead to different individualized treatment and different effects of treatment. Bioinformatical analysis is a method using gene chips in public database to analyze the characters of one type of disease; it can help researchers in better understanding the molecular mechanism behind different types of cancer [5][6][7], find new potential targets of early diagnosis and therapy [8,9], or discover new biomarkers for prognostic predictor [10,11]. At present, there are several predictive biomarkers for breast cancer, for example, triple-negative breast cancers (TNBC) which lack estrogen receptor (ER-), progesterone receptor (PR-), and amplification of human epidermal growth factor receptor 2 (HER2-).…”
Section: Introductionmentioning
confidence: 99%
“…The recently experimentally validated cancer types for this lncRNA included breast cancer [ 26 ] (using qRT-PCR), gastric cancer (by constructing a potential ceRNA network using bioinformatics tools and then validating the ADAMTS9-AS2/miR-372/CADM2 axis using qRT-PCR and dual luciferase reporter assay) [ 75 ], tongue squamous cell carcinoma (constructing ADAMTS9-AS2/miR-600/EZH2 ceRNA network) [ 79 ] and others. In contrast, only two recent studies on ADAMTS9-AS1 [ 71 , 72 ] with experimental validations have been found.…”
Section: Discussionmentioning
confidence: 99%